Long-read genome sequencing resolves complex genomic rearrangements in rare genetic syndromes - Iftekhar A. Showpnil; Maria E. Hernandez Gonzalez; Swetha Ramadesikan; Mohammad Marhabaie; Allison Daley; Leeran Dublin-Ryan; Matthew T. Pastore; Umamaheswaran Gurusamy; Jesse M. Hunter; Brandon S. Stone; Dennis W. Bartholomew; Kandamurugu Manickam; et al. (npj Genomic Medicine)
Abstract Long-read sequencing can often overcome the deficiencies in routine microarray or short-read technologies in detecting complex genomic rearrangements. Here we used Pacific Biosciences circular consensus sequencing to resolve complex rearrangements in two patients with rare genetic anomalies. Copy number variants (CNVs) identified by clinical microarray —chr8p deletion and chr8q duplication in patient 1, and interstitial deletions of chr18q in patient 2—were suggestive of underlying rearrangements. Long-read genome sequencing not only confirmed these CNVs but also revealed their genomic structures. In patient 1, we resolved a novel recombinant chromosome 8 (Rec8)-like rearrangement with a 3.43 Mb chr8q terminal duplication that was linked to a 7.25–8.21 Mb chr8p terminal deletion. In patient 2, we uncovered a novel complex rearrangement involving a 1.17 Mb rearranged segment and four interstitial deletions ranging from 9 bp to 12.39 Mb. Our results underscore the diversity of clinically relevant structural rearrangements and the power of long-read sequencing in unraveling their nuanced architectures.